1997
DOI: 10.1016/s0014-5793(97)00442-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of ERK activation by a novel monoclonal antibody

Abstract: The mitogen-activated protein kinase, ERK is activated by a dual phosphorylation on threonine and tyrosine residues. Using a synthetic diphospho peptide, we have generated a monoclonal antibody directed to the active ERK. The antibody specifically identified the active doubly phosphorylated, but not the inactive mono-or non-phosphorylated forms of ERKs. A direct correlation was observed between ERK activity and the intensity in Western blot of mitogen-activated protein kinases from several species. The antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 25 publications
2
96
1
Order By: Relevance
“…Erk2 is a serine/threonine kinase, which is activated by sequential phosphorylation on tyrosine and threonine residues (Yung et al, 1997). Although data presented here demonstrate a significant effect of TSP-1 on tyrosine phosphorylation of Erk2, this does not necessarily reflect an increase in the activity of the enzyme.…”
Section: Analysis Of Extracellular-regulated Kinase Activitycontrasting
confidence: 68%
“…Erk2 is a serine/threonine kinase, which is activated by sequential phosphorylation on tyrosine and threonine residues (Yung et al, 1997). Although data presented here demonstrate a significant effect of TSP-1 on tyrosine phosphorylation of Erk2, this does not necessarily reflect an increase in the activity of the enzyme.…”
Section: Analysis Of Extracellular-regulated Kinase Activitycontrasting
confidence: 68%
“…The PY20 antibody was purchased from Santa Cruz Biotechnology. A mAb to the active form of the MAP kinase (Yung et al, 1997) was a gift from R Seger (Weizmann Institute).…”
Section: Methodsmentioning
confidence: 99%
“…The biological differences we observed between epiregulin, EGF, and NDF in subsets of 32D cells suggested that these ligands may differ in signaling potency, and especially in their ability to recruit the MAPK pathway. To analyze receptor phosphorylation and MAPK activation we probed blots of whole extracts, prepared from ligandstimulated cells, with antibodies to phosphotyrosine, or with a murine mAb that specifically recognizes the active, doubly phosphorylated form of the ERK1 and ERK2 MAPKs (26). Surprisingly, the more mitogenic ligand of ErbB-1, epiregulin, exhibited weaker, but not less sustained, tyrosine phosphorylation of proteins at the 180-kDa range corresponding to ErbB-1 in D1 cells (Fig.…”
Section: Epiregulin Is a Relatively Potent Stimulator Of Erbb-1 But mentioning
confidence: 99%